1985
DOI: 10.1002/aic.690310402
|View full text |Cite
|
Sign up to set email alerts
|

A moving‐front transition boiling model

Abstract: In accordance with visual observations, a transition boiling model that assumes a quench front which alternately advances and retreats in the water flow direction, is proposed. With appropriate choice of a quench zone width and heat transfer rate when the surface is wet, the model predictions are in the same range as the observed temperature oscillations. SCOPEHeater wall temperature oscillations are characteristic of transition boiling. In flow boiling, the mechanism governing transition boiling depends on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1986
1986
1996
1996

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Messungen von Kao und Weisman [4,8] mit siedendem Wasser bei niedrigem Druck best/itigen im wesentlichen die hier bei einem Druck yon 5 bar erzielten Ergebnisse. Eine am ganzen Umfang auf gleicher H6he vorrfickende Flfissigkeitsfront mfigte daher positive Laufzeiten liefern.…”
Section: Ergebnisse Fiir Gegeniiber Angeordnete Thermoetementeunclassified
“…Messungen von Kao und Weisman [4,8] mit siedendem Wasser bei niedrigem Druck best/itigen im wesentlichen die hier bei einem Druck yon 5 bar erzielten Ergebnisse. Eine am ganzen Umfang auf gleicher H6he vorrfickende Flfissigkeitsfront mfigte daher positive Laufzeiten liefern.…”
Section: Ergebnisse Fiir Gegeniiber Angeordnete Thermoetementeunclassified
“…After a brief review of the steady state model, this note shows how the results of the steady state analysis for vertical surfaces may be used to obtain heat transfer rates during reflooding transients. Kao and Weisman (1985) concluded that during steady state transition boiling at high vapor fractions, intermittent wetting of a vertically oriented heater surface is primarily due to the vertical oscillation of the liquid film on the surface. That is, the upper edge of the liquid film moves up and down in a direction parallel to the vertical heater surface.…”
Section: Introductionmentioning
confidence: 98%